Dual-fluorescence pH probe for bio-labelling. Issue 45 (2nd November 2015) - Richter, C.; Schneider, C.; Quick, M. T.; Volz, P.; Mahrwald, R.; Hughes, J.; Dick, B.; Alexiev, U.; Ernsting, N. P.
Abstract : Seminaphtorhodafluor (SNARF) dyes usually contain a bulky phenyl group with an unspecific position of a second carboxy group. Here a smaller SNARF derivative is characterized spectroscopically, and efficient linkage to cysteine protein sites is demonstrated. Abstract : Although seminaphtorhodafluor (SNARF) dyes are already widely used to measure pH in cells and at biofilms, their synthesis has low yield and results in an unspecific position of a carboxy-group. The separation of 5′- and 6′-carboxy-SNARF reveals a p K a difference of 0.15, calling into question pH measurements with the (commercially available) mixture. Here we replace the bulky external dicarboxyphenyl ring with a propionate group and evaluate the spectral properties of the new derivative. Proceeding to the ethyl-iodoacetamide, covalent linkage to cysteine protein sites is achieved efficiently as shown with a cyanobacterial phytochrome, extending the scarce application of SNARF in bio-labelling in the current literature. Application in fluorescence lifetime imaging is demonstrated both with the lifetime-based and ratiometric-yield method.